ACTN3, Morbidity, and Healthy Aging - Pickering, Craig; Kiely, John (Frontiers in Genetics, 2018)
As human longevity increases, recent research has focused on the maintenance of optimal health during old age. One such area of focus is that of muscle function in the elderly, with a loss of muscle mass increasing the risk of negative outcomes such as sarcopenia and a decrease in bone mineral density. In this mini-review, we focus on the impact of a single nucleotide polymorphism in ACTN3, shown to impact muscle phenotype in elite athletes, on loss of muscle function, maintenance of bone mineral density, and metabolic disorder risk in an elderly population. From the surveyed research, this polymorphism has a clear and demonstrable impact on muscle phenotype and bone mineral density in this population, and acts as a potential modulator for metabolic disorders. As such, knowledge of an individual’s ACTN3 genotype may better inform the management of risk factors in the elderly, as well as driving innovations in exercise programme design. Subsequently, such insights may contribute to the prolonged maintenance of health and function long into old age.